The Effect of Secondary Care Intensity and Parental-Stress Toward Children Social-Emotional Development - Muhammad Azka Maulana; Benedikta Yunita; Aip Syarifudin (‎‎‎TAZKIYA Journal of Psychology, 2023)
This study aims to determine the effect of the intensity of secondary caregiver and parental stress on the socio-emotional development of early childhood secondary care intensity is the frequency of care where the other party cares more often than the biological parents. Here in after, parental stress is a condition where the primary care, in this case, the father or mother, experiences exhaustion in parenting. As of, there are two independent variables (secondary care intensity and parental stress) and a dependent variable (early childhood social-emotional development) with a linear regression technique. The secondary-caregiver intensity was measured based on self-reports from parents who reported the average daily routine regarding the intensity of care levels (whether more frequent primary or secondary care?). Furthermore, parental stress was measured using the parental role quality scale instrument to parents. Then, the measurement of children's social-emotional development is based on instruments from the Ages & Stages Questionnaire: Social-Emotional (ASQ: SE). The sample of this research was all parents of kindergarden X, and it was conducted by purposive sampling method. The use of statistical calculations that have been carried out with the linear regression method. The results showed that there was a significant effect of secondary care intensity and parental stress on children's social-emotional development using the ASQ: SE instrument. With this research, the author hopes that there will be further and in-depth research on social-emotional development with various other variables as well as conducting path analysis techniques in looking for a causal relationship between the intensity of secondary caregiver, parental stress, and social-emotional development of early childhood.